1999
DOI: 10.2139/ssrn.181668
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Risk at Year-End: Evidence from Interbank Lending

Abstract: Fax: +41 61 / 280 91 00 and +41 61 / 280 81 00This publication is available on the BIS website (www.bis.org). This paper analyses Risk premia on overnight interbank loans increase by a factor of 13 at year-end. Further, this finding is not consistent with common theories of similar year-end anomalies in other money markets. In particular, seasonal liquidity demands seem to explain only a fraction of the effect. Although evidence of yearend window dressing is found in the interbank market, such activity cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For the US, Furfine (1999) showed that the log of total Fed-wire fund transfers is positively significant in explaining federal fund rate changes. In a subsequent contribution (Furfine, 2000), the same author verified a significant positive correlation within the maintenance period between the federal funds daily rate and payment transfers, both in levels and volatility.…”
Section: Rossi and Tauchen 1992)mentioning
confidence: 99%
See 1 more Smart Citation
“…For the US, Furfine (1999) showed that the log of total Fed-wire fund transfers is positively significant in explaining federal fund rate changes. In a subsequent contribution (Furfine, 2000), the same author verified a significant positive correlation within the maintenance period between the federal funds daily rate and payment transfers, both in levels and volatility.…”
Section: Rossi and Tauchen 1992)mentioning
confidence: 99%
“…The same values for LCH were respectively 65% and 95% (the two CCPs merged in 2003). 20 The Table 17, p.28).…”
Section: Re-estimating the Model At Monthly Frequencymentioning
confidence: 99%
“…Window dressing is used by institution that want to appear more attractive near reporting periods and has been studied by several researchers. Furfine (1999) found a significant increase in the price in the federal funds market at year-end that for a part is due to window dressing. Heijmans et al (2013) find that Dutch money market rates contain a monthly calender effect, which indicates window dressing.…”
Section: The Lcr Statisticmentioning
confidence: 99%
“…These authors show that financial instruments maturing across the year-end trade at a discount. This effect is explained by the motivation of window dressing or higher demand for liquidity but Furfine (1999) argued that this effect can not be explained by these reasons.…”
Section: ∑ ∑mentioning
confidence: 99%
“…They also find some differences in the behavior of excess returns across holding periods of bonds. (Park and Reinganum, 1986;Allen and Saunders, 1992;Musto, 1997;Griffiths and Winters, 1997;Furfine, 1999). These authors show that financial instruments maturing across the year-end trade at a discount.…”
Section: ∑ ∑mentioning
confidence: 99%